SPK Kriteria Pemberian Bunus Tahunan Karyawan dengan Metode Simple Additive Weigthing - Weni Lestari Putri; Nanda Jarti (STMIK Budi Darma, 2022)
Annual Bonus is an award for employees who work at PT. Trust. Bonuses are given once a year. The problem that often occurs in giving bonuses is the difficulty of calculating the bonus to each employee who works at PT. The trust. The purpose of this study is to assist companies in providing bonuses to employees by looking at the criteria set by the company. The Simple Additive Weighting (SAW) method is the sum of all the weights of the performance of each object that is different but has the same opportunity with the criteria owned. The process of solving the algorithm using the Simple Additive Weighting (SAW) method uses a normalization process in the decision matrix (X) by comparing the alternative twig values owned. Variables that are used as a reference in giving bonuses are .1 Absence, 2. Working Period, 3. Attitude, Work Quality and Work Results. This method uses the SPK SAW method with a work process. The final result of the search process obtained the value of C1 = 1, C2 = 0.74, C3 = 1, C4 = 0.9 and C5 = 0.94 the names of employees in order 1 and 3 are prioritized to get the biggest annual bonus compared to other employees